Effectiveness of The Agriculture and Food Department in Developing The Food Security Sector in Yalimo Regency - Muhammad Sawir; Syarifuddin Hafid (Universitas Sultan Ageng Tirtayasa, 2020)
This research aims to determine the effectiveness of the Agriculture and Food Department in developing the food security sector in Yalimo Regency and what are the obstacles to its effectiveness. The research design uses qualitative methods with sources of information derived from internal and external informants Yalimo Regency Agriculture and Food Office using purposive sampling techniques. Data collection techniques through in-depth interviews, observation, and documentation. The results of the study note that the Agriculture and Food Service has not been effective in implementing the development of the food security sector in the Yalimo Regency. The formulation of the development goals of the food security sector that has been implemented has not been effective, because it has not yet had a direct impact on meeting the food needs of the community in the Yalimo Regency. The description of various activities that have been carried out is not on target because the production and productivity of some commodities supporting the food security sector are still low. The Department of Agriculture and Food in the development of food crop commodities only sees the output target and the preparation of various programs and activities not based on the availability of real data according to needs. Meanwhile, the breadth of tasks and authorities developed according to organizational structure, ability, and motivation of employees is still low, and the involvement of various parties in formulating food security policies is not a barrier to the effectiveness of the Agriculture and Food Service in developing the food security sector in Yalimo Regency.